Barriers to access to controls prenatal and birth institutionalized. Pinto Recodo, Lamas. 2014 - Zafra-Tanaka, Jessica Hanae (2015)
In developing countries complications during pregnancy and childbirth occur mostly in women who lacked of proper care during pregnancy (1). Therefore, the Ministry of Health aims to achieve a standardized management and quality of perinatal maternal health; thus defined as pregnant controlled that it has complied with 6 prenatal care and which received the basic package of care to pregnant women.